(3eNJUQ aj Yde GdefWbs - (3eMeO Hf jhSa Hf YeQ Hf TYjH GdMSfj GdSfhSj , CHh YHO Gddg, J (B895 (3g` s
(3ChdgG (B:s
(3hHYO agPg cJGHGJ eNJUQI JJVef eYQaI eG jNai Edjg ef Yde GdefWb s
(3BNQgG (B:s
(3hGdfJGFL ai gPG GdbjGS CQHYI s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B154 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B132s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(330 (3O(B) s
Keywords: (3GdadSaI hGdefWbs